Educational intervention applied in children from 5 to 11 years of age with deforming oral habits - María de los Santos Haces Yanes; Clotilde de la Caridad Mora Pérez; Nicolás Ramón Cruz Pérez; Ivette Alvarez Mora (Medisur)
Background: Habits are complex neuromuscular patterns learnt by frequent repetition and act as unnatural forces that may cause dental maxillofacial defects. Objective: To assess the intervention of educative measures applied to children with deforming buccal habits in the primary school Raúl Suárez Martínez from the zone “Rafaelito”. Methods: A cuasi-experimental study was developed, with before-after intervention without control group including 253 children from December 2006 to November 2007. We applied the program “To Happily Smile” with a weekly frequency. Surveys were applied to children, parents and teachers after the educational actions to achieve the reduction ofincorrect habits. The studied variables were: age, sex, deforming habits frequency before and after the intervention. Results: The knowledge level of children, parents and teachers was significantly improved. Risk factors were eradicated in more than 50% of the children being the most frequent: lingual protraction, baby bottle suction, mainly among females. Conclusions: The intervention was successful for the reduction of deforming oral habits, and the high level of knowledge acquired. After the intervention it was shown that the educative process is a key tool for the General Comprehensive Dentist.